KEBIJAKAN PENGELOLAAN LIMBAH PADAT BUKAN BERASAL DARI BAHAN BERBAHAYA DAN BERACUN MELALUI RE-USE ATAU RE-CYCLING UNTUK KELESTARIAN LINGKUNGAN HIDUP - Muhamad Ibnu Fajar; Nadiroh Nadiroh; Muzani Muzani (Jurnal Green Growth dan Manajemen Lingkungan, 2018)
This study aims to explain the policy of managing solid waste not from hazardous and toxic materials through re-use or re-cycling for environmental sustainability. This policy has been contained in the Bekasi district government regulation Number 09 of 2007. This policy is an effort in the management of non-B3 waste in order to become orderly and free from dirty and even slums. Through this policy the waste manager is required to be registered in the licensing of the waste management company, especially non-B3 solid waste. This study uses qualitative methods with consideration, researchers use questionnaires as consideration for determining the percentage scale of the success of waste management policies. Based on the results of the analysis of policies on the management of solid waste not derived from hazardous and toxic materials through re-use or reconstruction to preserve the environment, the results of 87.8% were converted into qualitative, including high and very good categories.